Dual mobility prosthesis for trapeziometacarpal osteoarthritis: results from a prospective study of 55 prostheses. (June 2023) - Falkner, Florian; Tümkaya, Arman Mahmut; Thomas, Benjamin; Panzram, Benjamin; Bickert, Berthold; Harhaus, Leila
This prospective study evaluated outcomes after trapeziometacarpal joint replacement with a dual mobility prosthesis (Touch®) in 55 thumbs (52 patients) with a mean follow-up of 25 months (range 12–36). Pre- and postoperative assessments included pain, range of motion, the Kapandji index, pinch- and grip strength, as well as functional scores and radiological parameters. Mean preoperative metacarpophalangeal joint hyperextension of 19° (range 15°–28°) showed a significant correction after 1 year with a mean value of 2° (range 0°–5°). Mean Quick Disabilities of the Hand, Shoulder and Arm score was 14 (range 6–28), and Michigan Hand Questionnaire 82 (range 67–92). No revisions due to infection, loosening, dislocation or material failure occurred during follow-up. The dual mobility trapeziometacarpal joint prosthesis was a reliable treatment option to decrease pain, improve motion, strength and pre-existing metacarpophalangeal joint hyperextension at short-term follow-up. Level of evidence: IV